Pursuing the wrong options? Adjustment costs and the relationship between uncertainty and capital accumulation. - Bond, S; Söderbom, M; Wu, G (Elsevier, 2011)
Abel and Eberly (1999) prove that uncertainty has an ambiguous effect on long run capital accumulation in a real options model. We show that, with adjustment costs quadratic in investment, more uncertainty reduces capital and this effect may be large.